2013
DOI: 10.1186/2050-7283-1-19
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in subjective memory impairment in a general population: the HUNT study, Norway

Abstract: Background: There is increased focus on early diagnosis of dementia, and subjective awareness of memory impairment is often assumed to be an early symptom of dementia. Subjective memory impairment (SMI) is used to describe subjective awareness of memory problems in the elderly after identifiable diseases which include this symptom are excluded. The aim of the present cross-sectional study was to examine the occurrence of SMI in a general adult population and its association with education level, subjective hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 26 publications
1
37
3
1
Order By: Relevance
“…Although a definition of SMC has not been operationalized numerous self‐report measures have been developed . In one large community survey, about half of individuals reported minor memory problems . In a UK survey, 31.7% reported forgetfulness in the last month, while 6.4% had forgotten something important in the last week .…”
Section: Introductionmentioning
confidence: 99%
“…Although a definition of SMC has not been operationalized numerous self‐report measures have been developed . In one large community survey, about half of individuals reported minor memory problems . In a UK survey, 31.7% reported forgetfulness in the last month, while 6.4% had forgotten something important in the last week .…”
Section: Introductionmentioning
confidence: 99%
“…All participants, both patients with dementia and normal elderly individuals, had participated in the third wave of the Nord‐Trøndelag Health survey (HUNT3) conducted in middle Norway from October 2006 to June 2008 and completed the subjective memory form (MMQ); The present study included two cohorts of patients with dementia from the Health and Memory Study (HMS); One cohort included all residents from nursing homes in Nord‐Trøndelag County evaluated as demented during 2010‐2011. The other cohort included all patients who had been diagnosed with dementia at any of the two Nord‐Trøndelag county hospitals between 1995 and 2010.…”
Section: Methodsmentioning
confidence: 99%
“…The Meta‐Memory Questionnaire (MMQ); was used in the HUNT3 epidemiological health survey to study subjective memory in Norway . A recent study using the MMQ in normal elderly individuals showed that this instrument measures two statistically independent components of SMCs, one related to long‐term declarative memory and the other related to short‐term working memory .…”
Section: Introductionmentioning
confidence: 99%
“…This has been found in several studies. [25][26][27][28] Others, however, found no such increase. 24,[29][30][31] It is also largely unknown, whether other sociodemographic (gender, educational attainment) and psychological variables (depressive symptomatology, neuroticism, cognitive performance), which have been identified in previous research as potentially influencing subjective memory/cognitive complaints, 11,24,32 are also relevant for the other cognitive domains.…”
Section: Introductionmentioning
confidence: 99%